Plasmablastic lymphoma as a rare cause of subocclusive events – case report and review of the literature - Lukic, Snezana; Dragasevic, Sanja; Zgradic, Sanja; Todorovic, Milena; Djuranovic, Srdjan; Andjelic, Bosko; Popovic, Dragan (Vojnosanitetski pregled, 2021)
Abstract Introduction. The most common causes of subocclusive disorders are the adhesion, Crohn's disease and small bowel neoplasms. Plasmablastic lymphoma (PBL) is an aggressive distinct subtype of diffuse large B-cell non-Hodgkin lymphoma initially reported in the oral cavity of the HIV infected individuals. Case report. We presented a male patient with PBL of the small intestine as a rare cause of intestinal subocclusion, without HIV infection and negative serology for hepatitis C, hepatitis B, and Epstein-Barr infection. A 73-year-old male was admitted to our Center due to the one-year history of abdominal pain, weigh loss, non-bloody diarrhea, night sweating and pruritus. The patient underwent the ileocolonoscopic examination with the accompanying biopsy specimens. The results, based on the histopathological and immunohistochemical pattern, confirmed a diagnosis of PBL. Following the chemotherapy treatment, our patient underwent the resection of ileum. The postoperative histopathological report confirmed PBL as the final diagnosis. The patient was treated for the following 6 months with the chemotherapy according to the cyclophosphamide, doxorubicin, vincristine, and prednisolone (CHOP) protocol. Fatal outcome was due to acute myocardial infarct. Conclusion. PBL of the small intestine is a rare and unusual cause of subocclusive events. In our patient, an accurate histopathological verification of the detected changes in the ileum was of crucial importance for further treatment
Keywords: crohn disease; diagnosis, differential; immunohistochemistry; intestinal neoplasms; intestinal obstruction; lymphoma, large b-cell, diffuse; plasmablastic lymphoma; treatment outcome